Boosting the biosynthesis of betulinic acid and related triterpenoids in Yarrowia lipolytica via multimodular metabolic engineering - Cong-Cong Jin (Microbial Cell Factories, 2019)
Abstract Background Betulinic acid is a pentacyclic lupane-type triterpenoid and a potential antiviral and antitumor drug, but the amount of betulinic acid in plants is low and cannot meet the demand for this compound. Yarrowia lipolytica, as an oleaginous yeast, is a promising microbial cell factory for the production of highly hydrophobic compounds due to the ability of this organism to accumulate large amounts of lipids that can store hydrophobic products and supply sufficient precursors for terpene synthesis. However, engineering for the heterologous production of betulinic acid and related triterpenoids has not developed as systematically as that for the production of other terpenoids, thus the production of betulinic acid in microbes remains unsatisfactory. Results In this study, we applied a multimodular strategy to systematically improve the biosynthesis of betulinic acid and related triterpenoids in Y. lipolytica by engineering four functional modules, namely, the heterogenous CYP/CPR, MVA, acetyl-CoA generation, and redox cofactor supply modules. First, by screening 25 combinations of cytochrome P450 monooxygenases (CYPs) and NADPH-cytochrome P450 reductases (CPRs), each of which originated from 5 different sources, we selected two optimal betulinic acid-producing strains. Then, ERG1, ERG9, and HMG1 in the MVA module were overexpressed in the two strains, which dramatically increased betulinic acid production and resulted in a strain (YLJCC56) that exhibited the highest betulinic acid yield of 51.87 ± 2.77 mg/L. Then, we engineered the redox cofactor supply module by introducing NADPH- or NADH-generating enzymes and the acetyl-CoA generation module by directly overexpressing acetyl-CoA synthases or reinforcing the β-oxidation pathway, which further increased the total triterpenoid yield (the sum of the betulin, betulinic acid, betulinic aldehyde yields). Finally, we engineered these modules in combination, and the total triterpenoid yield reached 204.89 ± 11.56 mg/L (composed of 65.44% betulin, 23.71% betulinic acid and 10.85% betulinic aldehyde) in shake flask cultures. Conclusions Here, we systematically engineered Y. lipolytica and achieved, to the best of our knowledge, the highest betulinic acid and total triterpenoid yields reported in microbes. Our study provides a suitable reference for studies on heterologous exploitation of P450 enzymes and manipulation of triterpenoid production in Y. lipolytica.